Application of Decision Support System in Recommendation for Determining the Best Music Platform for Generation Z - Agry Alfiah (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Music streaming services have become the primary choice for many users to enjoy music. However, with the multitude of options available, users often find it challenging to select the most suitable platform. This article discusses the application of the Simple Additive Weighting (SAW) method to evaluate and compare three popular music streaming services: Spotify, YouTube Music, and Apple Music. The assessment is based on five main criteria: audio quality, subscription price, ease of use, song selection and catalog, and application response time. Data were collected through a questionnaire involving 142 respondents. The analysis results indicate that Spotify excels in ease of use and song catalog selection, while YouTube Music stands out in terms of subscription pricing. By utilizing relevant criteria, this analysis aims to provide more informed recommendations for users. The SAW method has proven effective in generating objective and structured recommendations, helping users make better decisions when choosing a music streaming service.